(untitled) (International Seven Journal of Health Research, 2023)
Developmental dysplasia of the hip (DDQ) is an abnormality that affects the hip of the newborn. It can take several forms, such as an abnormal acetabular joint, which may or may not be associated with a subluxation or dislocation of the femoral head. The aims of this article are to analyze the possible influence of physiotherapeutic treatment on the rehabilitation of a patient diagnosed with hip dysplasia using a pavlik brace, based on a theoretical survey on the subject, to understand how the pavlik brace works and to list the kinesiotherapeutic activities performed on patients who use the pavlik brace to treat this comorbidity. This study is a case study carried out in the city of Ponto Belo - ES, where the importance of physiotherapy in the treatment of developmental dysplasia of the hip was explored. The research was carried out primarily through pediatric evaluation, observing the evolution and influence of physiotherapy after the use of the pavlik brace. Based on secondary articles on DDQ, these show various subjects on anatomy, definitions, pathophysiology, epidemiology, diagnosis and treatment. It can be concluded that treatment with the Pavlik brace has proved effective in patients diagnosed with CKD.